2005
DOI: 10.1080/02652030500197805
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous occurrence of some anabolic steroids in swine matrices

Abstract: Following findings of 17beta-19-nortestosterone (150-200 microg kg(-1)) in pigs of unspecified gender imported into the European Union, a study to determine steroid and hormone levels in swine from six age/gender categories (uncastrated 'old' boars, cryptorchids, one intersex, barrows, gilts and sows) was initiated. Indeed, for some hormones there has been a discussion about their being endo- or exogenous. Tissue and urine samples from swine from each of the six categories were obtained in Belgium, France, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 12 publications
2
20
0
Order By: Relevance
“…The analysis of urine samples collected from adult pigs in routine controls demonstrated the presence of endogenous 17bN in agreement with data described by other authors. 19,20,[35][36][37] The wide range of concentrations obtained for 17bN and its precursor, norandrostendione (Table 3), may be explained by the gender and the age of the animals providing the samples, in agreement with data recently published by other authors. 37 Information about the gender and the ages of the animals providing our samples was not available.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The analysis of urine samples collected from adult pigs in routine controls demonstrated the presence of endogenous 17bN in agreement with data described by other authors. 19,20,[35][36][37] The wide range of concentrations obtained for 17bN and its precursor, norandrostendione (Table 3), may be explained by the gender and the age of the animals providing the samples, in agreement with data recently published by other authors. 37 Information about the gender and the ages of the animals providing our samples was not available.…”
Section: Discussionsupporting
confidence: 88%
“…29,30 In non-treated calves, ABA and traces of NorE were detected. 15,21 17bN was also detected in non-castrated and cryptorchid male pigs, in testicular tissue and in urine from boars, [32][33][34] at very low concentrations in barrow and female pigs, 19,20,[35][36][37] and in the follicular fluid of sows. Detection of the consumption of anabolic agents is performed by the identification of specific metabolites using gas chromatography or liquid chromatography coupled to mass spectrometry (GC/MS, LC/MS) or to tandem mass spectrometry (MS/MS).…”
mentioning
confidence: 96%
“…Therefore, an official concentration threshold of free 17β-Bold at 15 ng/mL has been adopted, making mandatory the quantification of 17β-Bold in entire male urine (Ho et al, 2004). Bold is also considered to be endogenous in several other mammals, including man (Schänzer Female Gelding Thoroughbred other Unknown 0 1 0 6 0 2-5 8 1 0 6 3 6-10 2 5 3 3 6 11-16 3 5 2 0 6 17-33 0 1 3 0 4 Total 13 13 8 15 19 et al, 1994), cattle (Arts et al, 1996) and swine (Poelmans et al, 2005). Drug testing in horse faeces could be a good alternative to urine for testing anabolic steroids at breeding as faeces are much easier to collect from young animals.…”
Section: Introductionmentioning
confidence: 95%
“…As a matter of fact, meat is clearly one of the most naturally 'contaminated' foods (Maume et al, 2001;Maume et al, 2003;Poelmans et al, 2005a). Data published by Swan et al in 2007 already suggested that maternal beef consumption may alter males' testicular development in utero and adversely affect his adult reproductive capacity (Swan et al, 2007).…”
Section: Human Health and Hormonesmentioning
confidence: 99%
“…As regard to hormonal content, all foodstuff of animal origin contains steroid hormones and metabolites, but their concentrations vary with the kind of food, species, gender, age and physiological stage of the animal (Daxenberger et al, 2001;Poelmans et al, 2005aPoelmans et al, , 2005b. As a matter of fact, meat is clearly one of the most naturally 'contaminated' foods (Maume et al, 2001;Maume et al, 2003;Poelmans et al, 2005a).…”
Section: Human Health and Hormonesmentioning
confidence: 99%